Erythroblast transformation-specific 2 correlates with vascular smooth muscle cell apoptosis in rat heterotopic heart transplantation model - Liu, Xiaojuan; Yan, Daliang; Li, Yangcheng; Sha, Xilin; Wu, Kunpeng; Zhao, Jianhua; Yang, Chen; Zhang, Chao; Shi, Jiahai; Wu, Xiang (Journal of Thoracic Disease, 2016)
Background: Cardiac allograft vasculopathy (CAV) decreases the long-term survival of heart transplantation recipients. Vascular smooth muscle cell (VSMC) apoptosis is an important pathological feature of CAV. Erythroblast transformation-specific 2 (Ets-2), as a transcription factor, participates in cell apoptosis and plays an important role in organ transplantation. Methods: Hearts from Wistar-Furth (WF:RT1u) rats were heterotopically transplanted into Lewis (Lew:RT1l) rats without immunosuppression. Additional syngeneic heterotopic cardiac transplantations were performed in Lewis rats. HE staining was used to identify CAV. Ets-2 expression was examined by western blot. Ets-2 tissue location was examined by immunohistochemical assay and double immunostaining. Cleaved caspase 3 expression was detected by western blot. Co-localization of Ets-2 and cleaved caspase 3 was detected by double immunostaining. Ets-2, p53, cleaved caspase 3 and Bcl-xl expression in rat VSMC line A7R5 was examined after Ets-2 siRNA transfection. TUNEL assay was applied to detect A7R5 apoptosis with or without ETS-2 siRNA transfection. Immunoprecipitation was performed to explore the interaction between Ets-2 and p53. Results: Ets-2 expression decreased in the allograft group but had no obvious change in the isograft group. Meanwhile, the phenomenon of CAV was observed in the allograft group and there is neointima formation in the isograft group which is not obvious compared with allograft group. Additionally, Ets-2 expression was opposite to VSMC apoptosis in the allograft group. In vitro, Ets-2 siRNA transfection in A7R5cells resulted in enhanced cell apoptosis. Finally, Ets-2 interacted with p53. Conclusions: Ets-2 might inhibit VSMC apoptosis via p53 pathway. The results further elucidate the molecular mechanism of VSMC apoptosis after heart transplantation during CAV and provide theoretical basis for seeking new specific drug targets for CAV prevention and treatment.